PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP TURNOVER INTENTION PADA KARYAWAN PT.GITA RIAU MAKMUR PEKANBARU - Wati Linda; Sasmita2 Jumiati; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of job satisfaction, organizational commitment and organizational culture on turnover intention in employees of PT. Gita Riau Makmur Pekanbaru. The population in this study includes employees of the finance accounting, mechanics and marketing divisions at PT. Gita Riau Makmur Pekanbaru, totaling 85 people.Primary data was collected by questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using multiple linear regression analysis with the help of SPSS. The sampling technique that has been selected is the census method. The results showed that: 1) Job satisfaction had a negative and significant effect on turnover intention of employees of PT. Gita Riau Makmur Pekanbaru, 2) organizational commitment had a negative and significant effect on turnover intention of employees of PT. Gita Riau Makmur Pekanbaru, 3) organizational culture had a negative effect. and significant on turnover inetntion of employees of PT. Gita Riau Makmur Pekanbaru. 4) Job satisfaction, organizational commitment and organizational culture together have a significant effect on turnover intention in employees of PT. Gita Riau Makmur PekanbaruKeywords: job satisfaction, organizational commitment, organizational culture and turnover intention